2014
DOI: 10.1177/1043454214554656
|View full text |Cite
|
Sign up to set email alerts
|

High Validity and Reliability of the PedsQL™ Multidimensional Fatigue Scale for Brazilian Children With Cancer

Abstract: Among the main factors that affect patients' quality of life, fatigue is a significant symptom experienced by children during treatment. Despite the high incidence, there has been no validated scale to evaluate fatigue in children with cancer in Brazil. The purpose of this study was to examine the psychometric properties of the PedsQL™ Multidimensional Fatigue Scale, using self-reports of Brazilian children, 8 to 18 years of age, and proxy reports. A cross-sectional method was used to collect data from 216 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 36 publications
3
19
1
2
Order By: Relevance
“…Parent-child concordance was moderate to good amongst survivors, while we observed a low interrater reliability between parent and child reports for the healthy controls. Poor parent-child concordance for controls has also been reported in previous studies utilizing the PedsQL™ Multidimensional Fatigue Scale [38,39]. Survivors of BT having the highest concordance of all three groups, followed by survivors of ALL, could be caused by the severity of the disabilities associated with these two diagnoses.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Parent-child concordance was moderate to good amongst survivors, while we observed a low interrater reliability between parent and child reports for the healthy controls. Poor parent-child concordance for controls has also been reported in previous studies utilizing the PedsQL™ Multidimensional Fatigue Scale [38,39]. Survivors of BT having the highest concordance of all three groups, followed by survivors of ALL, could be caused by the severity of the disabilities associated with these two diagnoses.…”
Section: Discussionsupporting
confidence: 62%
“…In a recent systematic review of existing fatigue instruments, the authors concluded that the PedsQL™ Multidimensional Fatigue Scale was the only instrument among those studied with strong evidence of reliability [37]. Reliability and validity have been found to be stable across languages, age and gender [32,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Reliability ranged from 0.87 to 0.94,) except for sleep/rest fatigue (alpha=0.67). Cronbach alpha score was 0.90 for the total PedsQL Multidimensional Fatigue Scale, which was a little better than in recent studies in children (Varni et al, 2002a;Nascimento et al, 2015).…”
Section: Discussioncontrasting
confidence: 54%
“…The PedsQL Multidimensional Fatigue Scale was developed originally in English (Varni et al, 2002a). It has been translated to many languages such as Portuguese (Brazil) (Nascimento et al, 2015), Japanese (Kobayashi et al, 2011), and Dutch (Gordijn, Cremers, Kaspers, & Gemke, 2011). To the authors' The work to test the psychometric properties of this instrument was undertaken as part of a study to establish the links between self-esteem, fatigue and health-related quality of life in children with a diagnosis of cancer (The Authors 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The study was conducted on children aged 8-18 years as many as 216 respondents. The results of this study indicate that the level of reliability of Multidimensional Fatigue Scale instruments is from 0.70-0.90 for sleep/rest dimensions (children report shows α = 0,55) (Nascimento, et al, 2015).…”
Section: Methodsmentioning
confidence: 69%